The impacts of crop diversity and sustainable farming on food security, climate, and biodiversity in Dumanjug, Cebu, Philippines (Asian Journal of Agriculture, 2025)
Abstract. Lillo EP, Alcazar SMT, Malaki ABB, Chavez MLM, Cañarijo III DM, Redoblado BR, Margate MA, Diaz JL, Mago JE, Belanizo J, Beceril R, Revillas MJ, Abrigana M, Davirao C, Obando ME, Diaz GGG, Gonzaga CF, Cagara BN. 2025. The impacts of crop diversity and sustainable farming on food security, climate, and biodiversity in Dumanjug, Cebu, Philippines. Asian J Agric 9: 208-214. The Philippines, an archipelagic Southeast Asian country, faces a complex and interconnected set of challenges involving food security, biodiversity conservation, and sustainable agricultural practices. The impacts of climate change, the loss of crop diversity, and the reduction in agricultural output brought on by unsustainable farming practices are some of the country's complex issues. This study examines crop diversity and sustainable farming practices in Dumanjug, Cebu, Philippines, and their implications for food security, climate change adaptation, and biodiversity conservation. The research evaluates the farmer's diverse cropping systems and sustainable agricultural techniques by employing participatory observation and a survey questionnaire. Results highlight the reliance on local seeds, adoption of sustainable practices such as intercropping and crop rotation, and the cultivation of indigenous food crops like Cocos nucifera L., Moringa oleifera Lam., and Musa acuminata × balbisiana (ABB Group). Despite challenges such as typhoons, droughts, and limited resource access, these practices contribute to food security, economic stability, and ecosystem resilience. The study underscores the importance of promoting local seed systems, climate-resilient farming techniques, and supportive policies to address systemic vulnerabilities and enhance agricultural sustainability. The implementation of these recommendations is expected to bring about benefits such as increased crop diversity, improved food security, and enhanced resilience to climate change. Findings provide evidence-based recommendations for policymakers, agricultural extension workers, and local communities, contributing to regional and national efforts to achieve sustainable development goals.
Keywords: Agricultural resilience, Cebu, climate change adaptation, Dumanjug, local seeds, sustainable farming practices